(untitled) (Revista de Medicina Clinica, 2019)
Summary Background: Spinal nerve injury causes paralysis of the trapezius muscle, Its trajectory is superficial in the posterior triangle of the neck presenting susceptibility to be injured by iatrogenia, in the dissection of said region, being the most frequent cause. Five cases report: Four patients diagnosed with spinal nerve injury: Females aged 34, 42 and 48 years with a 4, 2 and 3 -year evolution respectively, after removal of the ganglion in supraclavical zone. A 27-year-old woman with a 1-year disease following emptying of cervical lymph nodes by thyroid cancer; A 28-year-old man with an evolution of 18 months after receiving direct trauma in the right supraclavicular region. In all cases presenting pain in shoulder, diagnosis was confirmed with EMG; by time of evolution transposition surgery is proposed for correction and improvement of function. Conclusion: If the immediate lesion is detected, the nerve reconstruction should be performed; if it does not improve in 6 months, neurolysis should be attempted; the procedure of Eden and Lange or the transposition of the sternum head from the pectoral to the scapula, as it corrects the deformity and improves the functionality. Keywords: spinal nerve injury; trapezius paralysis; neurolysis; nerve graftin; neurotization, muscle transposition.